Alcohol in primary health care: attitude of health professionals regarding the consumption and harmful use of alcohol and alcoholism - Magela, Natalia [UNESP]; Padovani, Flávia Helena Pereira [UNESP]; Sanine, Patrícia Rodrigues [UNESP] (FapUNIFESP (SciELO), 2023)
Factors associated with the attitudes of Primary Health Care (PHC) professionals regarding the consumption and harmful use of alcohol and the users’ alcoholism were evaluated, in addition to their perceptions about possible changes in alcohol consumption during the COVID-19 pandemic. This is an evaluative study conducted in the interior of São Paulo in 2020. Sociodemographic characteristics regarding alcohol consumption and attitude towards users were analyzed. A total of 65 of the 94 professionals in the municipality participated, with 67.7% of them having experience in the subject. Most (80%) did not change their consumption during the pandemic, but 50.8% noticed an increase in consumption by users. Positive attitudes towards being male (p=0.014) and having white skin color (p=0.020), living alone (p=0.047) and higher consumption by professionals (p=0.037) were identified. Acting in the Family Health Strategy (Estratégia Saúde da Família – ESF) was associated with more positive attitudes (p=0.029). In conclusion, personal characteristics influence the attitude, as well as the type of service. There is much to be done regarding the attitudes of health professionals to offer adequate care to users who consume alcohol. However, disseminating specific knowledge about the disease and the alcohol user seems to be one of the main coping strategies for this important health problem.
O álcool na atenção primária à saúde: atitude dos profissionais de saúde quanto ao consumo e uso prejudicial de álcool e o alcoolismo
Keywords: Alcohol Drinking; Alcoholism; Attitude of Health Personnel; Health Evaluation; Primary Health Care